Norcantharidin Nanoemulsion Development, Characterization, and In Vitro Antiproliferation Effect on B16F1 Melanoma Cells - Gabriel Martínez-Razo; Patrícia C. Pires; María Lilia Domínguez-López; Francisco Veiga; Armando Vega-López; Ana Cláudia Paiva-Santos (MDPI AG, 2023)
Melanoma is a highly lethal type of cancer that has had an increase in incidence in the last decades. Nevertheless, current therapies lack effectiveness and have highly disabling side effects, which calls for new therapeutic strategies. Norcantharidin (NCTD) is an acid derivative with potential antitumor activity isolated from natural blister beetles. However, its solubility limitations restrict its use. To address this issue, we developed an oil-in-water nanoemulsion using commonly available cosmetic ingredients, which increased NCTD solubility 10-fold compared to water. The developed nanoemulsion showed a good droplet size and homogeneity, with adequate pH and viscosity for skin application. In vitro drug release studies showed a sustained release profile, ideal for prolonged therapeutic effects. Accelerated stability studies proved that the formulation was reasonably stable under stress conditions, with particle separation fingerprints, instability index, particle size, and sedimentation velocity analyses being conducted. To assess the therapeutic potential of the developed formulation, in vitro studies were conducted on melanoma B16F1 cells; results showed an IC50 of 1.026 +/− 0.370 mg/kg, and the cells' metabolic activity decreased after exposure to the NCTD nanoemulsion. Hence, a new "easy-to-make" nanoformulation with therapeutic potential on melanoma cells was developed, as a possible adjuvant for future melanoma treatment.